Wound Treatment with 0.9% NaCl as an Effort to Prevent Infection in Post Operative Wounds in the Marwah Ward of PKU Muhammdiyah Karanganyar Hospital - Andriyani, Annisa; Utami, Sri; Novitasari, Azizah; Setyowati, Erika; Suhada, Alif Muhammad; Rahmawati, Anita; Yuniati, Anisa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
-